2008
DOI: 10.1176/appi.ap.32.4.332
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study and Evaluation of Postgraduate Course on "The Interface Between Spirituality, Religion and Psychiatry"

Abstract: The findings suggest improvement in the competency scores for residents and overall usefulness of this course; however, limited conclusions can be made due to a small sample size and lack of adequate comparison groups. Establishing educational significance will require gathering larger usable control data as well as validation of the Course Impact Questionnaire tool to distinguish between different skill levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 36 publications
0
41
0
1
Order By: Relevance
“…63 In fact, a significant number of U.S. psychiatry programs include a mandatory curriculum on R/S. 64 Nevertheless, a recent survey of Canadian psychiatry residencies found that almost 72% of Canadian programs did not offer residents training to prepare them to address the interface of R/S and psychiatry. 65 Given that patient belief systems play a key role in patient development and remain a powerful influence on responses to current illness and life demands, it is important that psychiatrists be aware of religious and spiritual issues.…”
Section: Challenges To Implementationmentioning
confidence: 99%
“…63 In fact, a significant number of U.S. psychiatry programs include a mandatory curriculum on R/S. 64 Nevertheless, a recent survey of Canadian psychiatry residencies found that almost 72% of Canadian programs did not offer residents training to prepare them to address the interface of R/S and psychiatry. 65 Given that patient belief systems play a key role in patient development and remain a powerful influence on responses to current illness and life demands, it is important that psychiatrists be aware of religious and spiritual issues.…”
Section: Challenges To Implementationmentioning
confidence: 99%
“…[134][135] Ways of introducing courses in spirituality in medical curricula and psychiatric residency programs in the United States and Canada have been well documented. [136][137] Scope and Boundaries of Professional Specialist Psychiatric Practice Defining boundaries, domains and roles will also have to result in the drafting of practical, ethical and professional guidelines for psychiatry and related disciplines. 138 What must be regarded as part of the scope of professional psychiatry should be clear and must be congruent with the general ethical principles that guide clinical practice.…”
Section: Training Of Spirituality In Psychiatrymentioning
confidence: 99%
“…Some studies have shown a relationship between well-being and spirituality. Research evidence has shown that spiritual activities lead to better outcomes in mental health and are effective in reducing the signs of stress, anxiety and depression [21]. Prayer and worship is one of the most important strategies in the spiritual individuals.…”
Section: Discussionmentioning
confidence: 99%